Clinical and epidemiological profile of premature patients in the ambulatory of pediatric ophthalmology of a university health service - Hino, Fabio Naoki; D’Amico Filho, Vitório Lauro; Agena, Jéssica; Duque, Wesley de Paula; Lima, Vagner Loduca (ABCS Health Sciences, 2020)
Introduction: Retinopathy of prematurity (ROP) is a vasoproliferative disorder of the retina that affects low birth weight preterm babies and is the leading cause of blindness in children in developed and developing countries. Objective: Considering the importance of evaluating the pathology, this study aimed to carry out an epidemiological analysis of premature patients referred to the Pediatric Ophthalmology sector of Centro Universitário FMABC. Methods: Retrospective study of the medical records of patients referred to the Pediatric Ophthalmology sector of Centro Universitário FMABC, from March 2017 to December 2017, for ophthalmological evaluation due to suspected ROP (59 medical records). Results: Of the total of 43 eyes with the disease, two eyes fit in Zone II and 41 in Zone III. Seventeen eyes were classified as Stage 1, 16 as Stage 2, 4 as Stage 3, 4 as Stage 4 and 2 as Stage 5. Conclusion: The development of ROP was inversely proportional to weight and gestational age at birth. Treatment proved to be less prevalent in the disease.